Pilot study on the use of infrared thermal imaging to predict infrainguinal bypass outcome in the immediate post-operative period. (December 2019) - Al Shakarchi, J; Inston, N; Dabare, D; Newman, J; Garnham, A; Hobbs, S; Wall, M
Objectives: Early bedside post-operative monitoring of infrainguinal bypass surgery is currently based on subjective clinical findings and handheld Doppler signals. Infrared thermal imaging is an objective and reproducible technique that has been proven to be a reliable and accurate method to measure skin temperature. The aim of this prospective study was to assess infrared thermal imaging as a predicting tool of bypass graft outcome in the immediate post-operative period and assess the angiosome concept. Methods: This was a prospective cohort study of 25 patients undergoing infrainguinal bypass. Demographic and clinical data were prospectively collected and included gender, age, co-morbidities, pre- and post-operative ankle brachial pressure indices, surgery undertaken and patency of run-off vessels. Infrared thermal imaging was undertaken pre- and post-operatively to assess thermal changes to the feet following revascularisation. Results: We found that an increase in temperature from pre- to post-operative was significantly associated with bypass patency. An increase in temperature was found to have a positive predictive value of 75%, a negative predictive value of 100%, a sensitivity of 100% and specificity of 89% for predicting graft patency. Conclusions: Infrared thermal imaging can be used to measure temperature related changes of the microcirculation post-operatively and predict bypass outcomes in the immediate post-operative period.